2019
DOI: 10.1155/2019/6521218
|View full text |Cite
|
Sign up to set email alerts
|

Phosphocreatine Improves Cardiac Dysfunction by Normalizing Mitochondrial Respiratory Function through JAK2/STAT3 Signaling Pathway In Vivo and In Vitro

Abstract: Diabetic cardiomyopathy (DCM) is one of the common cardiovascular complications in patients with diabetes. Accumulating evidence has demonstrated that DCM is thoroughly related to mitochondrial energy impairment and increases the generation of reactive oxygen species (ROS). Therefore, an ongoing study is developing strategies to protect cardiac mitochondria from diabetic complications, especially from hyperglycemia. Phosphocreatine (PCr) plays a major metabolic role in cardiac muscular cells including intracel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 48 publications
4
10
0
Order By: Relevance
“…Clinical studies have demonstrated a lower mitochondrial respiratory rate in the cardiac tissues of patients with diabetes (Croston et al, 2014;Montaigne et al, 2014). These findings also extend to experimental models of diabetic cardiomyopathy (Pham et al, 2014;Qaed et al, 2019). Consistent with previous studies, diabetic mice in this study exhibited similar reductions in LV mitochondrial oxygen consumption, particularly when measuring mitochondrial respiration by electron input through CII.…”
Section: Discussionsupporting
confidence: 90%
“…Clinical studies have demonstrated a lower mitochondrial respiratory rate in the cardiac tissues of patients with diabetes (Croston et al, 2014;Montaigne et al, 2014). These findings also extend to experimental models of diabetic cardiomyopathy (Pham et al, 2014;Qaed et al, 2019). Consistent with previous studies, diabetic mice in this study exhibited similar reductions in LV mitochondrial oxygen consumption, particularly when measuring mitochondrial respiration by electron input through CII.…”
Section: Discussionsupporting
confidence: 90%
“…The Sham group rats' chest was opened and the pericardium cut, while the thread was not ligated at the corresponding part. ST segment elevation of more than 1/2 and paleness of the front wall of the left ventricle on electrocardiogram were considered as the success of the AMI model [15]. At the same time, the NDRG4-overexpressing Ad constructed by Ki Gen Company was used for intramyocardial injection.…”
Section: Methodsmentioning
confidence: 99%
“…Mitochondrial respiration impairment is an important source for ROS in the development of DCM [ 35 ]. Phosphocreatine was found to improve oxidative phosphorylation and electron transport capacity in the mitochondria of diabetic hearts [ 36 ]. The findings that GCN2iB increased myocardial phosphocreatine content and the expression of genes involved in oxidative phosphorylation suggested that GCN2iB might decrease mitochondria-mediated ROS production by normalizing mitochondrial respiratory function.…”
Section: Discussionmentioning
confidence: 99%